Oral Cancer Awareness and Knowledge in the City of Valongo, Portugal. (7th August 2012) - Monteiro, Luís Silva; Salazar, Filomena; Pacheco, Júlio; Warnakulasuriya, Saman
Abstract : We conducted a questionnaire survey among 602 subjects in order to analyze the awareness and knowledge on oral cancer among residents of the city of Valongo in Portugal. The cancer that most subjects were aware of was breast cancer (99%). Oral cancer was the least mentioned cancer (68.6%). There was awareness of the relationship between oral cancer and smoking among 89.5% subjects, but less of the association with alcohol misuse (63.3%). Nonhealing mouth ulcers were identified as a sign or symptom of oral cancer by 90.0% and red or white patch by only 52.8% subjects. Whereas 94.5% agreed that early detection could improve the treatment outcome, a disheartening 28.1% believed that whether a person developed an oral cancer or not is a matter of luck and therefore is unavoidable. Surprisingly only 1.7% were ever submitted to or had knowledge of receiving a consultation regarding oral cancer. In conclusion, this survey demonstrates a general lack of awareness and knowledge on oral cancer in a population of Valongo. An oral health promotion strategy should involve elements of basic education on oral cancer for this population, and regular oral cancer screenings should be implemented in Valongo.